2006
DOI: 10.2138/am.2006.1880
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetics of cation ordering in natural and synthetic Mg(Al,Fe3+)2O4 spinels from in situ high-temperature X-ray diffraction

Abstract: Spinel-group minerals are characterized by a non-convergent, temperature-dependent cation order/disorder, i.e., no change of symmetry is associated with cation disordering. Cation distribution can be described by the IV (A 1-i B i ) VI (B 2-i A i )O 4 structural formula, where IV and VI represent the tetrahedrally and octahedrally coordinated T and M sites, respectively, A and B are cations with different valences, and i represents the inversion parameter. At low temperature, i tends to 0 in normal spinels [e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The plot of the unit-cell parameter vs. the Al content for both suites (Fig. 2) lies within the field defined by the regression lines belonging to the synthetic spinel sensu stricto-hercinite (Andreozzi and Lucchesi 2002) and spinel sensu stricto-magnesioferrite (Martignago et al 2006) joins. Figure 2 shows that the data from the two vol- Lucchesi et al 1998) spinels.…”
Section: Crystal Chemistrysupporting
confidence: 55%
See 1 more Smart Citation
“…The plot of the unit-cell parameter vs. the Al content for both suites (Fig. 2) lies within the field defined by the regression lines belonging to the synthetic spinel sensu stricto-hercinite (Andreozzi and Lucchesi 2002) and spinel sensu stricto-magnesioferrite (Martignago et al 2006) joins. Figure 2 shows that the data from the two vol- Lucchesi et al 1998) spinels.…”
Section: Crystal Chemistrysupporting
confidence: 55%
“…Figure 2 shows that the data from the two vol- Lucchesi et al 1998) spinels. Dotted line represents the data regression (R 2 = 0.945) of synthetic spinel sensu stricto-hercynite join (Andreozzi and Lucchesi 2002); dashed line represents the data regression (R 2 = 0.999) of synthetic spinel sensu stricto-magnesioferrite join (Martignago et al 2006 canic suites partially overlap, with the Somma-Vesuvius spinels higher in Al content, and brings out the crystal-chemical linking between the two sets of samples. With respect to the Alban Hills, the Somma-Vesuvius spinels are lower in Fe 3+ content, whereas the amounts of Fe 2+ are comparable.…”
Section: Crystal Chemistrymentioning
confidence: 99%
“…Throughout the temperature range investigated, no violations of space group symmetry were detected. Refinements were performed isotropically and ionized form factors were used for T and M cations, whereas neutral form factors were used for oxygen following refinement strategies already used in previous studies (Della Giusta et al, 1996;Salviulo et al, 2000;Martignago et al, 2006). Crystal-structure details are reported in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental studies on spinels have demonstrated that the kinetics of intracrystalline cation order-disorder is influenced by Fe 3+ and Cr contents as well as by non-stoichiometry (O'Neill 1994(O'Neill , 1997Harrison and Putnis 1999;Martignago et al 2006;Princivalle et al 2006Princivalle et al , 2012. In particular, the presence of Fe 3+ fosters the intracrystalline cation ordering process, because it was established that, in Fe 3+ -rich aluminate spinels, the Mg-Fe 3+ site exchange proceeds at higher speed and to lower temperature than the Mg-Al exchange ).…”
Section: Applicability Of Spinel Intracrystalline Geothermometry To Mmentioning
confidence: 99%